Middle-Paleozoic fragment of the appear polar wander path trajectory for the East European platform - Poliachenko, I.B. (Reports of the National Academy of Sciences of Ukraine, 2014)
Final results of paleomagnetic studies of gray-colored sediments and red beds of the Silurian and Lower Devonian from southwestern Ukraine (Podolia region, the Dniester River basin) are reported. New data indicate the location of the East European platform in the equatorial latitudes of the Southern Hemisphere in the Late Silurian and its drift to equatorial latitudes in the early Devonian followed by a drift in a southern direction. The drift velocity composes at least 3 cm/year. The drift peculiarity can be described as a counterclockwise rotation by 16º around the Euler pole with coordinates Φ = 46 ºS, Λ = 64 ºE.